ANALISIS PENGARUH KEADILAN ORGANISASI, KEPUASAN KERJA, DAN KOMITMEN ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) (Studi Pada Karyawan PT PLN Persero Distribusi Jawa Tengah & DIY) - Mustikasari, Intan Nofika; Rahardjo, Mudji (Faculty of Economics and Business Diponegoro University, 2016)
Employees play important role in running the company; almost all of the companies deem their respective employees as a part of competitive advantage. A company would highly expect to have employees with best behaviour as well as the ability to finish the entrusted tasks in excess of what is actually required. To put it simply, they are the employees who display extra-role behaviors which is often called as Organizational Citizenship Behavior (OCB). Without the existence of OCB, the company would be brittle and thus is in high risk to lose in the tight competition. This research is aimed to determine the direct, indirect, and total effects of organizational justice, job satisfaction, and organizational commitment on Organizational Citizenship Behavior (OCB) in a sample drawn from 71 employees of PT PLN Persero Distribusi Jawa Tengah dan DIY by spreading the questionnaires. The analytical method used on this research is path analysis with SPSS. Data analysis technique used consist of the value of index, validity and reliability test, classic assumption test, hypothesis testing by the determinant coefficient, F-test and T-test. The result of this research shows that organizational justice, job satisfaction, and organizational commitment have significant and positive effect on OCB, partially and simultaneously. Organizational Commitment has the biggest direct effects. The coefficient of determination shows that OCB of the employees in PT PLN Persero Distribusi Jawa Tengah dan DIY is 67,01% affected by organizational justice, job satisfaction, and organizational commitment. The other 32,99% is determined by other variables and error. Based on path analysis it is found out that job satisfaction and organizational commitment both hold a good role and significant as a mediator of organizational justice on OCB.